The Toronto Origins of Ontario’s 2008 Poverty Reduction Strategy: Mobilizing Multiple Channels of Influence for Progressive Social Policy Change - Hudson, Carol-Anne; Graefe, Peter (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2012)
This article provides an account of the community strategies that pushed the Ontario provincial government to pursue a poverty reduction strategy and attempted to shape that strategy as it developed. It pays particular attention to the tensions involved in developing a concerted and inclusive community campaign, both in terms of defining a shared programme, and balancing the geography of representation between Toronto organizations with a proximity to policy makers and organizations elsewhere in the province. While both presented challenges, it was ultimately the divisions of vision and strategy between social liberals and social democrats that proved the hardest to contain, especially as the provincial strategy was concretized and favoured the social liberal position.Cet article rend compte des initiatives communautaires qui ont poussé le gouvernement provincial de l'Ontario à adopter une stratégie de réduction de la pauvreté et des tentatives qui ont été faites pour la façonner au fil de son élaboration. Il porte une attention toute particulière aux tensions liées à la conception d'une campagne communautaire concertée et universelle : il s'agit en effet de définir un programme commun, mais aussi d'atteindre un équilibre en matière de représentation géographique entre les organismes de Toronto, proches des décideurs politiques, et ceux du reste de la province. Outre ces deux défis, ce sont finalement les divergences de vision et de stratégie entre les sociaux-libéraux et les sociaux-démocrates qui ont été les plus difficiles à maîtriser, en particulier au moment de la concrétisation de la stratégie provinciale qui a penché en faveur de la position des sociaux-libéraux.